Research training curriculum and projects undertaken by medical students in Australia and New Zealand - Joanne Hart; Adam Collison; Jon Cornwall; Natalie Edmiston; Di Eley; Kathryn Hird; Wendy Hu; Eleonora Leopardi; Christine Metusela; Lise Mogensen; Judy Mullan; Shannon Pike; et al. (BMC Medical Education)
Abstract Background Research training is vital to medical education, providing students with essential skills for their future evidence-based practice. Most medical programs worldwide include opportunities for students to implement projects. However, gaps remain in understanding how research training is delivered, integrated and assessed with project completion, and little data exists on the range of project types and topics. This study aims to document research training curricula across Australian and New Zealand medical schools and explore the types of projects undertaken by students. Methods An online survey of the 23 Australian and New Zealand medical school research training programs was undertaken. The survey recorded details about research training curriculum, project types and topics investigated. The titles of medical student projects completed in 2023 were collected and categorised using standard Australian Bureau of Statistics field of research codes and national health priority areas. Data were analysed using descriptive statistics. Results Eighteen medical programs responded to the survey (18/23, 78%). The survey responses identified various designs for research training curriculum, including coursework only, and combinations of coursework and different project options. Projects were mandatory in half the programs. Some programs facilitated an Honours year or intercalated higher degree by research. Projects were either integrated into coursework or stand alone, with 78% providing scheduled time to conduct the projects. The titles of 2024 medical student projects completed in 2023 were provided by 17 of the 18 participating medical schools. The research areas covered were broad, with most focusing on biomedical and clinical sciences (69%) or health sciences (20%). Additionally, 34% of the projects addressed Australian National Health Priority areas, with cancer control (28%) and mental health (26%) the most common topics. Conclusions This study provides a comprehensive overview of the current approaches to research training across medical programs in Australia and New Zealand. It highlights the diverse approaches to this aspect of medical education curriculum and the range of project types and topics undertaken by medical students. The findings provide valuable insights for medical curriculum developers and policymakers and can be used to inform research training practices and outcomes.